2023
DOI: 10.1021/acs.langmuir.3c01905
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Behavior of Droplet Impact on Laminar Superheated Particles

Abstract: The impact of droplets on particles involves a wide range of complex phenomena and mechanisms, including bubble nucleation, crater formation, fluidization, and more intricate changes in the boiling regime when impacting superheated particles. In this study, we focus on droplet impact behavior on superheated laminar particles at various temperatures and define six typical characteristic patterns of a single droplet impact on superheated laminar particles, including film evaporation, bubbly boiling, immersion bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Staat et al observed two transitions in the experimentally obtained phase diagram for impacting ethanol droplets and identified four boiling regimes including deposition, contact-splash, bounce, and film splash. Jiao et al focused on droplet impact behavior on the superheated laminar particles at various temperatures and defined six typical characteristic patterns, including film evaporation, bubbly boiling, immersion boiling, sputter boiling, transition boiling, and film boiling. The Leidenfrost point of droplets on the laminar superheated particles was found to decrease with the particle size, which was related to the effect of the pore space generated between the laminar particles.…”
Section: Introductionmentioning
confidence: 99%
“…Staat et al observed two transitions in the experimentally obtained phase diagram for impacting ethanol droplets and identified four boiling regimes including deposition, contact-splash, bounce, and film splash. Jiao et al focused on droplet impact behavior on the superheated laminar particles at various temperatures and defined six typical characteristic patterns, including film evaporation, bubbly boiling, immersion boiling, sputter boiling, transition boiling, and film boiling. The Leidenfrost point of droplets on the laminar superheated particles was found to decrease with the particle size, which was related to the effect of the pore space generated between the laminar particles.…”
Section: Introductionmentioning
confidence: 99%